Early-life programming of later-life brain and behavior: a critical role for the immune system - Bilbo, Staci D.; Schwarz, Jaclyn M. (Frontiers in Behavioral Neuroscience, 2009)
The immune system is well characterized for its critical role in host defense. Far beyond this limited role however, there is mounting evidence for the vital role the immune system plays within the brain, in both normal, “homeostatic” processes (e.g., sleep, metabolism, memory), as well as in pathology, when the dysregulation of immune molecules may occur. This recognition is especially critical in the area of brain development. Microglia and astrocytes, the primary immunocompetent cells of the CNS, are involved in every major aspect of brain development and function, including synaptogenesis, apoptosis, and angiogenesis. Cytokines such as tumor necrosis factor [TNF]α, interleukin [IL]-1β, and IL-6 are produced by glia within the CNS, and are implicated in synaptic formation and scaling, long-term potentiation, and neurogenesis. Importantly, cytokines are involved in both injury and repair, and the conditions underlying these distinct outcomes are under intense investigation and debate. Evidence from both animal and human studies implicates the immune system in a number of disorders with known or suspected developmental origins, including schizophrenia, anxiety/depression, and cognitive dysfunction. We review the evidence that infection during the perinatal period of life acts as a vulnerability factor for later-life alterations in cytokine production, and marked changes in cognitive and affective behaviors throughout the remainder of the lifespan. We also discuss the hypothesis that long-term changes in brain glial cell function underlie this vulnerability.